18th AIAA/ISSMO Multidisciplinary Analysis and Optimization Conference 2017
DOI: 10.2514/6.2017-3149
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Industrialization of New MDO Methodologies and Tools for Aircraft Design

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 18240 The aim of the project is to develop efficient capabilities (methods, tools and a software platform) to enable industrial deployment of MDO methods in industry. At IRT Saint Exupéry, industrial and academic partners collaborate in a single place to the development of MDO m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…In this section, the results of the visualization enhancements will be presented with regard to a tool repository containing a collection of DUT aircraft design tools. 9 This use case concerns the aerostructural optimization of an aircraft wing. The starting point of this case is a tool repository containing over 28,000 variables and over 37,000 data connections based on 29 function nodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the results of the visualization enhancements will be presented with regard to a tool repository containing a collection of DUT aircraft design tools. 9 This use case concerns the aerostructural optimization of an aircraft wing. The starting point of this case is a tool repository containing over 28,000 variables and over 37,000 data connections based on 29 function nodes.…”
Section: Resultsmentioning
confidence: 99%
“…XDSM The enhanced XDSM visualization developed in this research is based on the open-source XDSMjs package, which was released by Lafage in 2016 [9,18]. The main structure is the same as the conventional XDSM (see Fig.…”
Section: Visualization Techniques For Cmdows Filesmentioning
confidence: 99%
“…Methods compatible with the industrial settings are more likely to be accepted and applied in industry because they will have lower risks to implementation. One recent example is a version of the Bi-Level Integrated System Synthesis currently under development at IRT Saint Exupery [6]. A top level optimiser controls the shared design variables and domain level optimisers set the values for the local variables.…”
Section: Introductionmentioning
confidence: 99%
“…A top level optimiser controls the shared design variables and domain level optimisers set the values for the local variables. Over successive iterations between the two levels, Gazaix et al [6] showed that the process is able to converge to a feasible optimal result when applied to academic and industrial test cases. One of the main disadvantages of this method however is that the shared variables are exclusively controlled at a system level.…”
Section: Introductionmentioning
confidence: 99%
“…11 In particular, GEMS (Generic Engine for MDO Scenarios), an in-house Python framework, is used to generate the optimization processes and host the present methodology.…”
Section: Implementation Of the Architecturesmentioning
confidence: 99%